Mutations in the ENG, ACVRL1, and SMAD4 genes and clinical manifestations of hereditary haemorrhagic telangiectasia: experience from the Center for Osler’s Disease, Uppsala University Hospital - Torbjörn Karlsson; Honar Cherif (Upsala Journal of Medical Sciences, 2018)
Aim: The aim of this retrospective single-centre study was to evaluate whether mutations in the ENG, ACVRL1, and SMAD4 genes were associated with different phenotypes in hereditary haemorrhagic telangiectasia (HHT). Methods: The case records of 21 HHT patients with verified mutations in ENG, ACVRL1, or SMAD4 genes were reviewed. The numbers of HHT diagnostic criteria fulfilled for the three genotypes were compared, as was the prevalence of complications such as iron deficiency anaemia, gastrointestinal haemorrhage, stroke, and cerebral abscess. Results: Our results indicate that mutations in the ENG (HHT1), ACVRL1 (HHT2), and SMAD4 genes result in different HHT phenotypes. Epistaxis debuts earlier and may be more severe in HHT1 than in HHT2. The prevalence of pulmonary arteriovenous malformations (AVM) is higher in HHT type 1, whereas hepatic AVMs are more common in HHT2. One patient with mutations in both ENG and ACVRL1 genes was identified, as were two SMAD4-mutated patients suffering from the overlapping juvenile polyposis-HHT syndrome. Nearly one in five patients in our HHT population has been diagnosed with stroke or cerebral abscess, indicating a high prevalence of cerebral complications. Conclusion: Our results showing that ENG and ACVRL1 gene mutations result in different HHT phenotypes confirm the results from other HHT centres worldwide. Cerebral complications of HHT are common, underscoring the importance of regular screening for pulmonary AVMs and early intervention against such AVMs. We have identified an HHT patient with simultaneous mutations in the ENG and ACVRL1 genes. Surprisingly, this patient has had a mild course of the disease.